2017
DOI: 10.2166/wst.2017.536
|View full text |Cite
|
Sign up to set email alerts
|

Rheological and electrical properties used to investigate the coagulation process during sludge treatment

Abstract: Analyses of rheological properties and electrical conductivity (σ) at direct current have been employed in order to investigate the effects of calcium oxide on the coagulation process during sludge treatment in the textile industry. In this context, rheological and electrical measurements were performed on five samples - one that contained raw sludge and the other four that were prepared from the raw sludge and different amounts of calcium oxide: 2, 3, 4, 5% (w/w). Rheological behavior of these samples was ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…It's an effective method to study the rheological properties by using rheological model to fit the flow curves. A Herschel-Bulkley modified model was used to study rheological properties curves by A. Mortadi [23]. They studied the influence of CaO content on the rheological properties of sludge and well revealed the transition process of sludge coagulation process combined with electrical properties research [24,25].…”
Section: Tg-dsc Analysismentioning
confidence: 99%
“…It's an effective method to study the rheological properties by using rheological model to fit the flow curves. A Herschel-Bulkley modified model was used to study rheological properties curves by A. Mortadi [23]. They studied the influence of CaO content on the rheological properties of sludge and well revealed the transition process of sludge coagulation process combined with electrical properties research [24,25].…”
Section: Tg-dsc Analysismentioning
confidence: 99%
“…In eqn (3), and are the complex permittivities of the medium and the particle, respectively, with and , ω is the angular frequency, ε m and ε p are the permittivities of the medium and the particle, respectively, and σ p and σ m are the conductivities of the medium and the particle, respectively. 45 To calculate the Clausius–Mossotti factors in this work, the conductivity measurements at 25.5 °C and pH 7.4 revealed that the conductivity of 10 mM Tris was 410 μS cm −1 , whereas the conductivity of 40% iodixanol at 25.9 °C was determined to be 65.2 μS cm −1 . However, parameters such as the permittivity of particles and the medium are challenging to measure due to variations in dielectric constants of exosomes depending on their sources, composition, and experimental conditions.…”
Section: Methodsmentioning
confidence: 98%